Antitumor activity of docetaxel-loaded polymeric nanoparticles fabricated by Shirasu porous glass membrane-emulsification technique - Yu YN; Tan SW; Zhao S; Zhuang XT; Song QL; Wang YL; Zhou Q; Zhang ZP (International Journal of Nanomedicine, 2013)
Yunni Yu,1,* Songwei Tan,1,2,* Shuang Zhao,1 Xiangting Zhuang,1 Qingle Song,1 Yuliang Wang,1 Qin Zhou,2,3 Zhiping Zhang1,2 1Tongji School of Pharmacy, 2National Engineering Research Center for Nanomedicine, 3College of Life Science and Technology, Huazhong University of Science and Technology, Wuhan, People’s Republic of China *These authors contributed equally to this work Abstract: Docetaxel (DTX) has excellent efficiency against a wide spectrum of cancers. However, the current clinical formulation has limited its usage, as it causes some severe side effects. Various polymeric nanoparticles have thus been developed as alternative formulations of DTX, but they have been mostly fabricated on a laboratory scale. Previously, we synthesized a novel copolymer, poly(lactide)-D-α-tocopheryl polyethylene glycol 1000 succinate (PLA-TPGS), and found that it exhibited great potential in drug delivery with improved properties. In this study, we applied the Shirasu porous glass (SPG) membrane-emulsification technique to prepare the DTX-loaded PLA-TPGS nanoparticles on a pilot scale. The effect of several formulation variables on the DTX-loaded nanoparticle properties, including particle size, zeta potential, and drug-encapsulation efficiency, were investigated based on surfactant type and concentration in the aqueous phase, organic/aqueous phase volumetric ratio, membrane-pore size, transmembrane cycles, and operation pressure. The DTX-loaded nanoparticles were obtained with sizes of 306.8 ± 5.5 nm and 334.1 ± 2.7 nm (mean value ± standard deviation), and drug-encapsulation efficiency of 81.8% ± 4.5% and 64.5% ± 2.7% for PLA-TPGS and poly(lactic-co-glycolic acid) (PLGA) nanoparticles, respectively. In vivo pharmacokinetic study exhibited a significant advantage of PLA-TPGS nanoparticles over PLGA nanoparticles and Taxotere. Drug-loaded PLA-TPGS nanoparticles exhibited 1.78-, 6.34- and 3.35-fold higher values for area under the curve, half-life, and mean residence time, respectively, compared with those of PLGA nanoparticles, and 2.23-, 13.2-, 8.51-fold higher than those of Taxotere, respectively. In vivo real-time distribution of nanoparticles was measured on tumor-bearing mice by near-infrared fluorescence imaging, which demonstrated that the PLA-TPGS nanoparticles achieved much higher concentration and longer retention in tumors than PLGA nanoparticles after intravenous injection. This is consistent with the pharmacokinetic behavior of the nanoparticles. The tumor-inhibitory effect of DTX-loaded nanoparticles was observed in vivo in an H22 tumor-bearing mice model via intravenous administration. This indicated that PLA-TPGS nanoparticles are a feasible drug-delivery formulation with a pilot fabrication technique and have superior pharmacokinetic and anticancer effects compared to the commercially available Taxotere. Keywords: SPG membrane emulsification, nanoparticles, docetaxel, pharmacokinetics, antitumor activity